2012
DOI: 10.1080/17470218.2011.604786
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Attention among Working Memory Representations: Testing Cue Type, Awareness, and Strategic Control

Abstract: It is well known that visual working memory (VWM) performance is modulated by attentional cues presented during encoding. Interestingly, retrospective cues presented after encoding, but prior to the test phase also improve performance. This improvement in performance is termed the retro-cue benefit. We investigated whether the retro-cue benefit is sensitive to cue type, whether participants were aware of their improvement in performance due to the retro-cue, and whether the effect was under strategic control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
127
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(147 citation statements)
references
References 37 publications
15
127
1
4
Order By: Relevance
“…On the face of it, the retro-cue appears to be largely an endogenous shift of internal attention. However, recent findings indicate that purely exogenous (abrupt onset retro-cues) and purely endogenous (number retro-cues mapped to a spatial location) cues do not elicit a retro-cue benefit; instead endogenous/exogenous hybrids such as arrow retro-cues are required (Berryhill et al, 2011). It is also essential to note that the retro-cue paradigm and associated attentional cuing effects are distinct from Sperling's classic partial report research because the timing is well beyond the defined limits of iconic memory (<500 ms) (Sperling, 1960).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…On the face of it, the retro-cue appears to be largely an endogenous shift of internal attention. However, recent findings indicate that purely exogenous (abrupt onset retro-cues) and purely endogenous (number retro-cues mapped to a spatial location) cues do not elicit a retro-cue benefit; instead endogenous/exogenous hybrids such as arrow retro-cues are required (Berryhill et al, 2011). It is also essential to note that the retro-cue paradigm and associated attentional cuing effects are distinct from Sperling's classic partial report research because the timing is well beyond the defined limits of iconic memory (<500 ms) (Sperling, 1960).…”
mentioning
confidence: 99%
“…Berryhill et al (2011) reported no retro-cue benefit when the number or peripheral retro-cues were used, even though these cues induce shifts of perceptual attention. Makovski and Jiang (2007) also noted behavioral differences while using single or multiple retro-cues to indicate one or more locations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, those studies have shown that directing attention to the location of one previously encoded stimulus using retrocues subsequently enhances the recall of that stimulus (Berryhill, Richmond, Shay & Olson, 2012;Delvenne, Cleeremans, & Laloyaux, 2010;Griffin & Nobre, 2003;Landman, Spekreijse & Lamme, 2003;Lepsien, Griffin, Devlin & Nobre, 2005;Lepsein & Nobre, 2006;Makovski & Jiang, 2007;Makovski, Sussman & Jiang, 2008;Matsukura, Luck & Veraca, 2007;Nobre et al, 2004;Tanoue & Berryhill, 2012;Tanoue, Jones, Peterson & Berryhill, 2013, amongst others). Recent electrophysiological evidence suggests that retro-cues promote the selective access of relevant VSTM representations and bias processing in favour of those representations (Kuo, Stokes & Nobre, 2012).…”
Section: Introductionmentioning
confidence: 99%